Estrategias de innovación en el Almacén “Voluntad De Dios” ubicado en la Parroquia Ricaurte del Cantón Urdaneta periodo 2022. - Mosquera Lucas, Genesis Yulisa (2023)
The present case study called "Innovation strategies in the Voluntad de Dios Warehouse period 2022 located in the Ricaurte parish of Cantón Urdaneta" related to the line of research "Financial, Administrative, Tax, Audit and Control Management" and the sub-line of the "Marketing and Commercialization" career, its objective is to analyze the innovation processes of the Voluntad de Dios fabric store through information acquired from the period 2022 to identify business growth. To carry out this work, the problems presented by the store were identified, such as lack of a prestigious corporate image, lack of interest in offering discounts and promotions, it does not have a website or advertising on social networks, as well as it does not use electronic commerce. For the investigation of this case, the descriptive method was used in order to take different data, in order to obtain a correct analysis of the proposed topic, the techniques of this study were a survey form carried out on real and potential clients and the interview the business owner and the instruments used to obtain the necessary information were a 10-question form to survey customers and a 7-question form to interview the store owner. In conclusion, the degree of innovation is very deficient in this small company and the degree of conformity of the customers when buying in this business is half efficient because they do not feel totally satisfied with the products and materials that it offers them, since this business it does not adapt to your tastes and preferences in the same way it does not update to the market, fashion and trends.